2019
DOI: 10.1186/s12903-019-0735-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep-disordered breathing and associations with orofacial symptoms among Saudi primary school children

Abstract: BackgroundThis study aimed to determine the prevalence of sleep-disordered breathing among primary school children in Riyadh, Saudi Arabia, and to evaluate associations between sleep-disordered breathing and respiratory conditions/orofacial symptoms.MethodsIn this cross-sectional study, 1600 questionnaires were distributed to Saudi boys and girls aged 6–12 years from 16 primary schools in Riyadh. The questionnaire covered relevant demographic and personal characteristics, presence of respiratory conditions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 44 publications
4
37
3
2
Order By: Relevance
“…Allergic inflammation of the nasal mucosa will result in nasal congestion, which may lead to oral breathing patterns and sleep fragmentation and may also lead to an increased risk of asthma exacerbation. Chronic rhinosinusitis and adenoid hypertrophy are common accompanying diseases in children with AR, which may be one of the reasons why AR is a high risk factor for sleep disordered breathing [ 30 , 43 45 ]. Hence, nasal congestion is a treatable cause of SRBD in children [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Allergic inflammation of the nasal mucosa will result in nasal congestion, which may lead to oral breathing patterns and sleep fragmentation and may also lead to an increased risk of asthma exacerbation. Chronic rhinosinusitis and adenoid hypertrophy are common accompanying diseases in children with AR, which may be one of the reasons why AR is a high risk factor for sleep disordered breathing [ 30 , 43 45 ]. Hence, nasal congestion is a treatable cause of SRBD in children [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PSQ is a multi-page questionnaire that consists of closed question-items and several queries on pediatric sleep disorder symptoms. This questionnaire has frequently been used for research [1,11,12,14,16,18,[22][23][24][25]. It comprises 22 questions on snoring, sleepiness, and behavioral problems.…”
Section: Sleep and Respiratory Datamentioning
confidence: 99%
“…This result is also consistent with the high prevalence of reported pediatric SDB symptoms among the general Saudi population. [ 7 12 ] where it reached 21% among School-children in Baidas study. [ 12 ] This study is the first study to report the prevalence of sleep-disordered breathing symptoms among the orthodontic population in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that about 21% of Saudi children are at risk of sleep-disordered breathing and the prevalence of snoring was 14.4%. [ 12 ] These two studies indicate that Saudi children, in general, have a higher risk of developing SDB symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation